The Arizona State Constitution - Leshy, John D. (Oxford commentaries on the state constitutions of the United States., 2013)
In The Arizona State Constitution, John D. Leshy provides a comprehensive history of Arizona's constitutional development. Adopted at the height of the progressive movement, the Constitution contains many progressive innovations. Leshy describes these along with the dramatic changes the state has undergone in subsequent decades. He also includes a section-by-section commentary which crisply discusses the evolution and interpretation of each section, including significant court decisions. Thoroughly updated to reflect amendments and court cases through the fall of 2012, the second edition of Th.